Photoswitchable water-soluble quantum dots: PcFRET based on amphiphilic photochromic polymer coating - Diaz, Sebastian Andres (2011)
A novel surface architecture was developed to generate biocompatible and stable photoswitchable quantum dots (psQDs). Photochromic diheteroarylethenes, which undergo thermally stable photoconversions between two forms with different spectral properties in organic solvents, were covalently linked to an amphiphilic polymer that self-assembles with the lipophilic chains surrounding commercial hydrophobic core-shell CdSe/ZnS QDs. This strategy creates a small (∼7 nm diameter) nanoparticle (NP) that is soluble in aqueous medium. The NP retains and even enhances the desirable properties of the original QD (broad excitation, narrow emission, photostability), but the brightness of its emission can be tailored by light. The modulation of emission monitored by steady-state and time-resolved fluorescence was 35-40%. The psQDs exhibit unprecedented photostability and fatigue resistance over at least 16 cycles of photoconversion.